Cross-sectional association of oxidative balance score with cataract among US adults: NHANES 1999–2008 - Li, Ning; Fan, Yuchen; Li, Juan; Guo, Juanjuan; Wang, Jianfeng; Gao, Ziqing (Frontiers in Nutrition, 2025)
ObjectiveOxidative stress plays a crucial role in the onset and progression of cataracts. As a comprehensive indicator of an individual’s oxidative stress status, OBS integrates dietary antioxidant intake and lifestyle factors, providing a holistic assessment of oxidative-antioxidative balance. However, research on the association between OBS and cataracts remains limited. Therefore, our study aims to bridge this research gap and provide novel epidemiological evidence supporting the role of oxidative stress in cataract prevention.MethodsA total of 13,409 subjects from the National Health and Nutrition Examination Survey (NHANES) conducted between 1999 and 2008 were selected. The OBS was calculated based on 16 dietary factors and 4 lifestyle factors. Weighted logistic regression and restricted cubic splines (RCS) were employed to assess the association between OBS and cataract.ResultsThe prevalence of cataract was found to be 12.2%. The restricted cubic spline analysis did not support a non-linear association between OBS and the prevalence of cataract (p = 0.742). After categorizing participants into quartiles based on OBS, those in the Q4 group exhibited lower odds of developing cataract (OR: 0.827, 95% CI: 0.713, 0.958, p < 0.01) compared to the Q1 group. Subgroup analysis revealed that significant associations were observed only among males, individuals with an education level below high school, those with a poverty income ratio (PIR) ranging from 1.3 to 3.49, and individuals with a Charlson comorbidity index (CCI) of 2 or higher.ConclusionThe OBS demonstrated a strong negative correlation with cataract prevalence. These results underscore the importance of adhering to an antioxidant-rich diet and lifestyle for cataract prevention, as well as the need to consider individual and population-specific factors in future research and prevention strategies.